Electromechanical Peak Devices of Distributed Power Generation - S. V. Konstantinova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The power world crises (1973, 1979) have demonstrated that mankind entered the expensive energy epoch. More and more attitude is given to power saving problem by including renewable power sources in energy balance of the countries. The paper analyzes a power system inBelarusand a typical chart of the active load is cited in the paper. Equalization of load chart is considered as one of measures directed on provision of higher operational efficiency of power system and power saving.  This purpose can be obtained while including electromechanical peak devices of the distributed generation in the energy balance.